Consumer exposures to laser printer-emitted engineered nanoparticles: A case study of life-cycle implications from nano-enabled products. Issue 6 (September 2015) - Pirela, Sandra V.; Sotiriou, Georgios A.; Bello, Dhimiter; Shafer, Martin; Bunker, Kristin Lee; Castranova, Vincent; Thomas, Treye; Demokritou, Philip
Abstract It is well established that printers emit nanoparticles during their operation. To-date, however, the physicochemical and toxicological characterization of "real world" printer-emitted nanoparticles (PEPs) remains incomplete, hampering proper risk assessment efforts. Here, we investigate our earlier hypothesis that engineered nanomaterials (ENMs) are used in toners and ENMs are released during printing (consumer use). Furthermore, we conduct a detailed physicochemical and morphological characterization of PEPs in support of ongoing toxicological assessment. A comprehensive suite of state of the art analytical methods and tools was employed for the physicochemical and morphological characterization of 11 toners widely utilized in printers from major printer manufacturers and their PEPs. We confirmed that a number of ENMs incorporated into toner formulations (e.g. silica, alumina, titania, iron oxide, zinc oxide, copper oxide, cerium oxide, carbon black among others) and released into the air during printing. All evaluated toners contained large amounts of organic carbon (OC, 42–89%), metals/metal oxides (1–33%), and some elemental carbon (EC, 0.33–12%). The PEPs possess a composition similar to that of toner and contained 50–90% OC, 0.001–0.5% EC and 1–3% metals. While the chemistry of the PEPs generally reflected that of their toners, considerable differences are documented indicative of potential transformations taking place during consumer use (printing). We conclude that: (i) Routine incorporation of ENMs in toners classifies them as nano-enabled products (NEPs); (ii) These ENMs become airborne during printing; (iii) The chemistry of PEPs is complex and it reflects that of the toner and paper. This work highlights the importance of understanding life-cycle (LC) nano-EHS implications of NEPs and assessing real world exposures and associated toxicological properties rather than focusing on "raw" materials used in the synthesis of an NEP.